Keunggulan Komparatif Sektor Pertambangan Dan Penggalian di Kabupaten Bojonegoro Berdasarkan Perhitungan Analisis Location Quotient - Achmad Andi Leanado; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The mining and excavation sector in the components of the gross regional domestic product (PDRB) in Bojonegoro Regency is still the backbone of regional income and also development in Bojonegoro Regency, starting from infrastructure development and human development index (HDI). In research with the mining and excavation sector variable which is the base sector using the location quotient (LQ) calculation. This leading sector in Bojonegoro Regency has many impacts on its region starting from regional original income (PAD) and also other income components as well as impacts on society and also progress in development in Bojonegoro Regency.